План «Барбаросса» - Гадеев, А.В. (Культура народов Причерноморья, 2013)
В статье рассматриваются планы Гитлера в отношении Советского Союза, стремление Гитлера завоевать новое жизненное пространство. План нападения на СССР появился у Гитлера после победы над Францией. Пакт с СССР был для Гитлера лишь временным инструментом, облегчающим Германии реализацию ее ближайших военно- политических целей. С разгромом СССР Гитлер решал для себя две основные задачи. Во-первых, он уничтожил советскую мощь, добивался гегемонии в континентальной Европе. Во-вторых, и это главное, Гитлер получал земли и ресурсы на Востоке, без которых Германия не могла достичь мирового господства. Предполагалось, что военная мощь России будет уничтожена еще до наступления осенней распутицы. Все приготовления сводились в подготовке исключительно летней кампании, которая должна была привесит к политическому разложению большевистского государства и к разделу России на мелкие государства. Несмотря на серьезную подготовку, немцы просчитали не все. Огромные пространства России, мощный экономический потенциал, людские ресурсы, способность к мобилизации, профессиональные военачальники, духовные силы народа – вот что не учли разработчики плана «Барбаросса». У статті розглядаються плани Гітлера щодо Радянського Союзу, прагнення Гітлера завоювати новий життєвий простір. План нападу на СРСР з'явився у Гітлера після перемоги над Францією. Пакт з СРСР був для Гітлера лише тимчасовим інструментом, що полегшує Німеччині реалізацію її найближчих військово-політичних цілей. З розгромом СРСР Гітлер вирішував для себе дві основні задачі. По-перше, він знищив радянську міць, домагався гегемонії в континентальній Європі. По-друге, і це головне, Гітлер отримував землі і ресурси на Сході, без яких Німеччина не могла досягти світового панування. Передбачалось, що військова міць Росії буде знищена ще до настання осіннього бездоріжжя. Всі приготування зводилися до підготовки виключно літньої кампанії, яка повинна була привести до політичного розпаду більшовицької держави і до розділу Росії на дрібні держави. Незважаючи на серйозну підготовку, німці не все прорахували. Величезні простори Росії, потужний економічний потенціал, людські ресурси, здатність до мобілізації, професійні воєначальники, духовні сили народу - ось що не врахували розробники плану «Барбаросса». The article considers the plans of Hitler against the Soviet Union, Hitler's desire to win new vital space. A plan of attack on the USSR appeared to Hitler after the victory over France. The Pact with the USSR was for Hitler only a temporary tool to facilitate Germany's implementation of its closest military-political goals. With the defeat of the USSR, Hitler decided to two main tasks. First, he destroyed the Soviet power, sought hegemony in continental Europe. Secondly, and most importantly, Hitler received land and resources in the East, without which Germany could not achieve world domination. The meaning of aggression against the USSR is revealed in the work of «Mein Kampf», where Hitler wrote: «Germany will either become a world power, or would cease to exist. But to become a world power, it will need a size that is at the present time to give it the necessary importance and its citizens - life... When in Europe, we are talking about new lands, first of all, we can only think about Russia». Thus, the Eastern vector of German aggression was constant regardless. Was Russia антигерманской coalition (First world war) or has been (in the case of the USSR) partner of Germany (at the beginning of the Second world war). It was assumed that the military power of Russia will be destroyed before the onset of autumn impassability of roads. All the preparations were merged in the preparation of a purely summer campaign, which was привесит to the political decomposition of the Bolshevik state and to the section of Russia into small States. Despite the serious training, the Germans calculated not all. The enormous expanse of Russia, powerful economic potential, human resources and ability to mobilize, professional military leaders, spiritual strength of a nation is not taken into account by the developers of the plan «Barbarossa».